Pathfinding by identified growth cones in the spinal cord of zebrafish embryos - Kuwada, JY (J Neurosci, 1990)
The spinal cord of early (18–20 hr) zebrafish embryos consists of a small number of neurons per hemisegment. The earliest neurons are identified and project growth cones that follow stereotyped, cell- specific pathways to reach their termination sites. We have studied the pathways taken by 4 of the early neurons in order to delineate the cells and structures their growth cones encounter during pathfinding. These neurons are 3 classes of commissural neurons (CoPA, CoSA, and CoB), which have contralateral longitudinal axons, and the VeLD neuron, which has an ipsilateral longitudinal axon. These growth cones encounter a defined set of cells and structures. Commissural growth cones appear to bypass the longitudinal axons of several identified neurons, including those from contralateral commissural neurons they encounter immediately following projection from the cell bodies. In contrast, these growth cones appear to extend in association with the longitudinal axons of commissural cells after crossing the ventral midline. Another set of cells of interest are the floor plate cells, a row of cells that constitute the ventral floor of the cord. At the floor plate growth cones exhibit cell-specific behaviors which may be influenced by the floor plate. (1) The floor plate may attract specific growth cones. The CoPA, CoSA, CoB, and VeLD growth cones all extend to the floor plate while other identified growth cones do not. (2) The floor plate may mediate cell-specific turns and induce some growth cones to cross the midline while inhibiting others from doing so. The commissural growth cones extend directly under the floor plate to cross the midline and turn anterior (CoPA and CoSA) or bifurcate (CoB); the VeLD growth cone turns away from the midline and extends posteriorly. (3) The floor plate may mediate changes in the substrate affinities of growth cones. Commissural growth cones bypass longitudinal pathways before they have encountered the floor plate, but not after. The description of pathfinding by these growth cones suggests that some elements in their environment are ignored while others are not. Most interestingly, a single structure (the floor plate) may mediate multiple, cell-specific effects on spinal growth cones.